APPROACHES OF PROBING SIGNAL TYPE DETERMINATION OF MEANS LOCAL PROBING FOR THIS STUDY IS DEVOTED TO SUBSTANTIATING THE STRUCTURE OF THE DEVICE OF THE TECHNICAL CONDITION OF ELECTRICAL DISTRIBUTION NETWORKS - GONCHARENKO, YURII; KOVBASYUK, SERGII; POLESCHUK І.; TEPTYA, VIRA; PRYADKO, V. (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The structure of the device for diagnostics of technical condition of power transmission lines is considered in the work and its functional scheme is offered. The article describes the principle of operation of the diagnostic device according to the functional diagram. The scheme of power lines with three branches and timestamps from known places with inhomogeneities in the sounding of the main diagnostic device and the scheme of power lines with three branches and timestamps from known places that have inhomogeneities in the sounding of auxiliary sounding are considered. The proposed device for diagnosing the technical condition of power distribution networks is based on the method of processing a radar signal with frequency modulation of a continuous wave. Unlike existing devices, this device allows you to detect faults in certain areas of branched transmission lines; has low output power. The use of a software-tuned radio station in the development and production of a diagnostic device significantly reduces material costs. it is necessary to diagnose high-voltage power lines with a large number of branches, as well as to study areas of inhomogeneity with small amplitudes of reflected signals. This paper substantiates the structure and principle of operation of the location sensing device for assessing the technical condition of electrical distribution networks in ice. The novelty is the use of special broadband signals for sounding and their optimal processing, in determining the location of damage (heterogeneity) in the branched overhead power lines, which are the basis of the diagnostic device of the transmission line. The diagnostic device can become a basis for the creation of the modern all-Ukrainian dispatching point of the analysis of a technical condition and management of the equipment of electric networks by power supply lines.